Low blue light hazard for tunable white light emitting diode with high color fidelity and circadian performances. (March 2021) - Nie, Jingxin; Chen, Zhizhong; Jiao, Fei; Zhan, Jinglin; Chen, Yifan; Chen, Yiyong; Pan, Zuojian; Kang, Xiangning; Wang, Yongzhi; Wang, Qi; Zhou, Tianhang; Dang, Weimin; et al.
Highlights: Mixing purple and azure LEDs obtains blue light perception and reduces its hazard. New algorithm is developed to reduce independent variables in mixed light simulation. BLHER of the mixed white light at 2500 to 7000 K is straight low as 0.06. High color fidelity and circadian performances with tunable CCT are achieved. Abstract: Referring to the standard of International Electrotechnical Commission (IEC), purple and azure light emitting diodes (LEDs) are used to obtain the blue vision and avoid the blue light hazard (BLH). In order to get the high color fidelity for mixed white LED, the other monochromatic LEDs are chosen according to the CIE 1931 chromaticity diagram and Grassmann Color Law of additive color mixture. Using the mathematical model of monochromatic LEDs and restrictions of chromaticity coordinates on Planckian blackbody locus, there are only 2 independent variables in the simulation to a certain combination of peak wavelengths. The optimized peak wavelengths of the five monochromatic LEDs are 385, 467, 524, 564, and 632 nm. The blue light hazard efficiency of radiation (BLHER) of the practical mixed white light is always less than 0.06 when its correlated color temperature (CCT) changes from 2500 to 7000 K. The BLHER is as low as the incandescent lamp at 2700 K and is much lower than other conventional lighting sources. The measured color rendering index (CRI), color fidelity score (Rf), and color gamut score (Rg) of the mixed white light are more than 84.9, 80.4, and 98.1, respectively. The circadian action factor (CAF) is measured as from 0.23 to 0.89 in the above CCT ranges. At last, the limitations of this work and some potential solutions are discussed.